Electronically Governed ROMP: Expanding Sequence Control for Donor–Acceptor Conjugated Polymers - Koehler, Stephen J.; Hu, Jinzhen; Elacqua, Elizabeth (Synlett, 2020)
Controlling the primary sequence of synthetic polymers remains a grand challenge in chemistry. A variety of methods that exert control over monomer sequence have been realized wherein differential reactivity, pre-organization, and stimuli-response have been key factors in programming sequence. Whereas much has been established in nonconjugated systems, π-extended frameworks remain systems wherein subtle structural changes influence bulk properties. The recent introduction of electronically biased ring-opening metathesis polymerization (ROMP) extends the repertoire of feasible approaches to prescribe donor–acceptor sequences in conjugated polymers, by enabling a system to achieve both low dispersity and controlled polymer sequences. Herein, we discuss recent advances in obtaining well-defined (i.e., low dispersity) polymers featuring donor–acceptor sequence control, and present our design of an electronically ambiguous (4-methoxy-1-(2-ethylhexyloxy) and benzothiadiazole-(donor–acceptor-)based [2.2]paracyclophanediene monomer that undergoes electronically dictated ROMP. The resultant donor–acceptor polymers were well-defined (Đ = 1.2, Mn > 20 k) and exhibited lower energy excitation and emission in comparison to ‘sequence-ill-defined’ polymers. Electronically driven ROMP expands on prior synthetic methods to attain sequence control, while providing a promising platform for further interrogation of polymer sequence and resultant properties.1 Introduction to Sequence Control2 Sequence Control in Polymers3 Multistep-Synthesis-Driven Sequence Control4 Catalyst-Dictated Sequence Control5 Electronically Governed Sequence Control6 Conclusions
Keywords: ring-opening metathesis polymerization; organic synthesis; sequence controlled; polymer chemistry; conjugated polymers; paracyclophane; donor–acceptor